2011
DOI: 10.1017/s0033291711002388
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of social difficulties, acculturation and persistent depression in Pakistani women living in the UK

Abstract: Lack of acculturation, especially less familiarity with the English language, is an independent predictor of persistence of depression in Pakistani women in UK. This needs to be taken into consideration when planning treatment, which also needs to address the personal difficulties associated with persistent depression. The implication of this work is that women of Pakistani origin with depression should be encouraged to receive help in the use of English as one part of treatment that may prevent relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…The median age was 29 years. Seventy percent held associate or higher degrees and 60% were engaged in the labor force with a median income of $60,000 and a poverty rate of 17% (Census, 2014). The largest concentrations settled in New York, New Jersey, Illinois, California and Texas (Census, 2014).…”
Section: Migration Of Pakistani Immigrants To the Usmentioning
confidence: 99%
See 3 more Smart Citations
“…The median age was 29 years. Seventy percent held associate or higher degrees and 60% were engaged in the labor force with a median income of $60,000 and a poverty rate of 17% (Census, 2014). The largest concentrations settled in New York, New Jersey, Illinois, California and Texas (Census, 2014).…”
Section: Migration Of Pakistani Immigrants To the Usmentioning
confidence: 99%
“…A highly esteemed family member usually an older male, other than the father, recites the azan, the Muslim call to prayer, into the ear of the baby soon after birth. The azan represents the first words heard by the newborn (Chaudhry, Husain, Tomenson, & Creed, 2012). Another common practice is feeding the baby ghutti (first taste of food) soon after birth.…”
Section: Cultural Beliefs and Practices In Pregnancy And Childbirthmentioning
confidence: 99%
See 2 more Smart Citations
“…An independent predictor of the persistence of depression in Pakistani women has been reported to be the lack of acculturation, particularly less familiarity with the English language [7]. A British study explored the experience of maternity service among first-and second-generation Pakistani women, and although the study observed no clear intergenerational differences, it found that women with a limited or insufficient network or language barriers have additional needs [8].…”
Section: Introductionmentioning
confidence: 99%